2015
DOI: 10.4103/0971-4065.139097
|View full text |Cite
|
Sign up to set email alerts
|

Liver biopsy in patients on hemodialysis with hepatitis C virus infection: An important tool

Abstract: Hepatitis C virus (HCV) infection is commonest blood borne infection amongst hemodialysis patients. Still, there is paucity of data on liver biopsy in these patients. Our center is doing regular liver biopsy in these patients and thus thought of sharing our experience. In this retrospective study, all patients with HCV infection on hemodialysis were subjected to liver biopsy. Serum bilirubin, liver enzyme, HCV-PCR, genotype and viral load measurement were done in all. Biopsy specimen was stained with H and E, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… 10 Patients with positive anti-HCV antibodies were further investigated for their qualitative HCV RNA, HCV viral load, and HCV genotype as described previously. 10 Because of our previous experience of only 1 patient with histological cirrhosis, 11 we clinically assessed the activity of liver disease, and no patient underwent liver biopsy. Before starting treatment, hemoglobin, total leukocyte count, differential leukocyte count, platelets, reticulocyte counts, and alpha fetoprotein were assessed in all patients using standard methods.…”
Section: Methodsmentioning
confidence: 99%
“… 10 Patients with positive anti-HCV antibodies were further investigated for their qualitative HCV RNA, HCV viral load, and HCV genotype as described previously. 10 Because of our previous experience of only 1 patient with histological cirrhosis, 11 we clinically assessed the activity of liver disease, and no patient underwent liver biopsy. Before starting treatment, hemoglobin, total leukocyte count, differential leukocyte count, platelets, reticulocyte counts, and alpha fetoprotein were assessed in all patients using standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…Details of liver biopsy in our set-up of patients had been published elsewhere. [ 24 ] None of the patients had raised bilirubin and/or clinical hepatitis at presentation. Other investigations of patients done before start of treatment are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously published studies of Peg-INF monotherapy in these patients are shown in Table 3 for comparative analysis. [ 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 ] The goal of the treatment of HCV-infected patient is to reduce all-cause mortality and liver-related health adverse consequences, including end-stage liver disease and hepatocellular carcinoma, by achieving virological cure as evidenced by an SVR. Although patients treated with either conventional or Peg-IFN-a have similar efficacy and safety results on the basis of meta-analysis studies, one head-to-head randomized trial showed that the overall efficacy and safety in patients treated with Peg-IFN-a were superior to those treated with conventional IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In a study from north India, genotype 3 was the commonest in CKD patients on hemodialysis. 17 In our study genotype 1 was predominant in CKD patients on hemodialysis, which is in trend with geographical prevalence. In CKD patients genotype 1 was seen in 93.1% and genotype 3 in 6.9% of patients.…”
mentioning
confidence: 85%
“…Very few studies have reported genotype in these patients. [15][16][17] In two western studies genotype 1 was commonest. 15,16 In a study from north India, genotype 3 was the commonest in CKD patients on hemodialysis.…”
mentioning
confidence: 99%